Bioequivalence of Two Misoprostol Tablets in Healthy Chinese Female Volunteers: A Single-Dose, Two-Period, Double Crossover Study - Huang, J.; Chen, R.; Li, R.; Wei, C.-M.; Yuan, G.-Y.; Liu, X.-Y.; Wang, B.-J.; Guo, R.-C. (Arzneimittelforschung, 2012)
To assess the bioequivalence of a new generic formulation of misoprostol (CAS 59122-46-2) 0.2 mg tablets (test) and the available branded tablet (reference) for the requirement of state regulatory criteria and the marketing of the test product in China.A randomized-sequence, 2-period crossover study was conducted in 20 healthy Chinese female volunteers in the fasted state. Blood samples were collected at baseline and 0.083, 0.17, 0.25, 0.33, 0.5, 0.75, 1, 1.25, 1.5, 2, 3, 4 and 6 h after a single oral dose of 0.6 mg misoprostol test or reference, followed by a 7-day washout period. Misoprostol acid, the active metabolite of misoprostol, was determined by an HPLC-MS/MS method. Drug And Statistics 2.0 was used to calculate the pharmacokinetics parameters and assess bioequivalence of the 2 formulations. It was considered bioequivalent if the 90% CIs of the mean ratios (test: reference) for Tmax, Cmax and AUC0–t were all within the range from 80% to 125%. Adverse events were monitored throughout the study based on clinical parameters and patient reports.The main pharmacokinetics parameters for the test and reference were as follows: t1/2 was (0.680±0.371) h and (0.650±0.264) h; Tmax was (0.415±0.087) h and (0.399±0.097) h; Cmax was (1.941±0.417) ng/mL and (2.047±0.397) ng/mL; AUC0–t was (1.535±0.419) ng·h/mL and (1.652±0.400)ng·h/mL, and the AUC0–∞ was (1.576±0.465) ng·h/mL and (1.686±0.396) ng·h/mL. The mean ratios (test: reference) for Cmax, AUC0–t, and AUC0–∞ were 95.3%±13.2%, 92.65%±17.31%, and 93.61%±18.97%, respectively. No significant (p>0.05) differences in pharmacokinetic parameters were found between preparations, treatments and periods.This single-dose study in healthy Chinese fasted volunteers was shown that the misoprostol test and reference met the requirement of US and China regulatory criterion, and the test and reference were bioequivalent.
Keywords: HPLC/MS/MS; pharmacokinetics; bioequivalence; misoprostol; misoprostol acid